FORMATION OF STUDENTS' DISCIPLINE CHARACTER IN TECHNOLOGY-BASED LEARNING OF CREED AND MORALS IN SCHOOLS (PIONIR: JURNAL PENDIDIKAN, 2025)
In the digital and globalization era, education is not only required to produce students who are intellectually intelligent, but also have strong Islamic character and morals. This study aims to analyze the role of Islamic Religious Education (PAI) teachers in shaping students' disciplined character through technology-based Akidah Akhlak learning and to identify strategies, obstacles, and the context of learning implementation in schools. This study uses a qualitative approach with a case study method, involving 13 PAI teachers and 5 students at various levels of education from elementary/Islamic elementary school (SD/MI), junior high/Islamic junior high school (SMP/MTs), to senior high school (MA/SMA). Data collection techniques were carried out through in-depth interviews and participatory observation, while data analysis used the stages of data reduction, data presentation, and drawing and verifying conclusions with source triangulation. The results of the study indicate that the use of technology, such as Islamic digital media, learning videos, interactive applications (Wordwall, Quizizz), and AI platforms have made a positive contribution to improving student discipline. Teachers implemented strategies such as project-based learning, digital role models, and the habituation of moral values. However, various obstacles have been identified, such as limited infrastructure, a lack of digital skills among teachers, and difficulties in monitoring and measuring moral values ​​in the digital environment. Therefore, teacher training, improved facilities, and an integrative approach that combines technology with Islamic values ​​are needed to realize effective and contextual character education.Keywords: Moral Creeds, Educational Technology, Disciplined Character, Digital Learning